Extraction of Fibre from Furcraea foetida Leaves and Their Evaluation - Kumari, Moni; Sarkar, Smriti Rekha (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted from November to December of the year 2022 to extract the fibre from the Furcraea foetida leaf. Furcraea foetida plants are planted on the DRPCAU campus as ornamental plants and were selected for the present study. Furcraea foetida is a perennial subshrub plant that grows 4-6 feet tall and has the potential to extract natural, eco-friendly cellulosic fibres from its leaves. Furcraea foetida fibres were extracted by using the retting method in three different conditions: control (W), urea (U1), and urea (U2). It was observed that the U1 completed their retting in 10 days, and also, it became more yielding. U1 finished its retting in 12 days, while the control retting took longer. Fibre yield was higher in U2. This indicates that the use of urea significantly enhances the retting process and improves fibre yield compared to traditional methods. The results suggested that optimising retting conditions with urea could lead to more efficient production of Furcraea foetida fibres for various applications. The fibre analysis revealed high cellulose, moderate lignin, and low ash content, with moisture levels progressively decreasing across samples. These compositional traits indicate strong structural integrity and reduced impurities. When retting was optimized, efficiency improved significantly, leading to higher output and better quality fibre. This underscores the importance of selecting appropriate retting techniques, as method choice directly influences productivity and material performance. Overall, the findings highlight how fibre composition and processing strategies together determine effectiveness and yield in production.